QORAQALPOG‘ISTON HUDUDINING GEOGRAFIK O‘RGANILISH TARIXI - Ya.Radjapov, M.; Eshimbetov, U.X. (SCIENCE and SOCIETY, 2024)
The article analyzes data from the history of the geographical study of the territory of Karakalpakstan, gives an idea of their significance.